Molecular epidemiology of bla CTX-M gene-producing uropathogenic Escherichia coli among Iranian kidney transplant patients: clonal dissemination of CC131 and CC10 - Mehrdad Halaji; Shahrzad Shahidi; Behrooz Ataei; Abdolamir Atapour; Awat Feizi; Seyed Asghar Havaei (BMC, 2021)
Abstract Background This study aimed to investigate the phylogenetic characterization and virulence traits of uropathogenic Escherichia coli (UPEC) isolated from kidney transplant patients (KTPs) as well as non-KTPs and analyze the clonal distribution of Extended spectrum β-lactamases (ESBLs)-producing UPEC containing bla CTX-M gene. Methods To this end, we determined virulence marker and the phylogenetic characterization of UPEC in non-KTPs (n = 65) and KTPs (n = 46). The non-KTPs were considered the control group of the study. Also, according to the Achtman scheme, we performed multilocus sequence typing to assess the relationship between twenty-nine of ESBL-producing isolates containing bla CTX-M gene. Results According to the results of PCR assay, the prevalence of virulence factor genes ranged from 0% (cnf and papG III) to 93.7% (fimH). Also, KTP isolates significantly differed from non-KTP isolates only in terms of the prevalence of pap GI elements. Moreover, the most frequent UPEC isolates were in phylogenetic group B2, followed by group D (18.9%), and group A (13.5%). Furthermore, except for phylogenetic group C, there was no significant correlation between phylogenetic distribution in KTPs and non-KTPs. Additionally, MLST analysis of bla CTX-M carrying isolates identified 18 unique sequence types (ST) the most common of which was ST131 (24.1%), followed by ST1193 (10.3%), while fourteen STs were detected only once. Conclusions The results further revealed significant differences between the UPEC isolates from KTPs and non-KTPs regarding the phylogroups C and PAI gene. Based on MLST analysis, we also observed a relatively high diversity in UPEC isolates obtained from KTPs and non-KTPs. Moreover, clonal complex (CC) 131 and ST131 were found to be the most prevalent clones and ST types, respectively. Besides, for the first time, ST8503 were reported in KTPs. These results suggested regular studies on characterization of UPEC isolates among KTPs.